DIMENSI KEAGAMAAN DALAM MIGRASI LIGKUNGAN: STUDI KASUS DUA KOMUNITAS MUSLIM DI PESISIR UTARA JAWA - Pratisti, Siti Aliyuna; Bagir, Zainal Abidin; Ahimsa-Putra, Heddy Shri; Northcott, Michael S. (LIPI Press, 2023)
This research discusses environmental migration of two Muslim communities in the North Coast of Java as they facing abrasion and coastal flooding. The concept of environmental migration is employed to scrutinised communities’ decision and process of relocation to avoid drowning condition of their village. Two Muslim communities, Bedono in Demak, Central Java, and Pantai Bahagia in Bekasi, West Java, are selected as the two communities show religious feature in their migration process. Research method apply qualitative case study by conducting interviews and 12 months observation. Findings show that in Bedono community, the Kiai Mudzakir Tomb, play significant role in decision making for out migration. While in Pantai Bahagia, Pengajian provide social connection and sense of belonging for those who relocated. Further analysis on environmental migration shows that religious dimension contributed in shaping the close relocation pattern found in both community.